PENGARUH PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE JIGSAW DISERTAI TREE CHART TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP NEGERI 1 LEMBAH GUMANTI - Hayati, Dian; Risdawati, Renny; Suheni, Suheni (Pendidikan Biologi, 2013)
ABSTRACTÂ Those problems above can be over coned by the implementation of Cooperative Learning model using Jigsaw tipe and Tree Chart. The research purpose is to find out the studentâs study result in class VII junior high school number one Lembah Gumanti. The researt type is experimental research, where as the research population is the students of class VII semester II junior high school number one Lembah Gumanti in the study year of 2012/2013 consisting of six class. The sample taking uses the technive of purposive sampling resulting in two sample classes namely class VIIc as experimental class and class VIId as control class. The data analysis technigve is by testing average finilarity using test-t on the real level 0,05. Where as the data analisis result shows the price tcount 2,924 and ttable 1,674 meaning that tcount > ttable, there fore the hypotesis is accepted. Finaly the research can be congluded that by using Cooperative Learning model with Jigsaw type and Tree Chart can inprove the study result of biology in class VII junior high school number one Lembah Gumanti regency of Solok.Â Â